Pelaksanaan Penerapan Diversi pada Kasus Perkara Tindak Pidana Penganiayaan oleh Anak di Kepolisian Sektor (Polsek) Pemulutan Ogan Ilir - Hernawan Hurairo; Hambali Yusuf; Cholidi Zainuddin (Jurnal Hukum Lex Generalis, 2025)
The handling of child abuse cases often presents new challenges. To address this, the government has issued regulations concerning children in conflict with the law. This study examines the implementation of diversion in child abuse cases at the Pemulutan Ogan Ilir Sector Police and the obstacles investigators face. Using an empirical and descriptive-analytical approach, the study finds that while diversion efforts align with Law No. 11 of 2012 and Law No. 17 of 2016, they remain ineffective due to difficulties in reaching agreements. Additional challenges include investigator professionalism, limited resources, and societal perceptions favoring imprisonment as the best punishment.